IPTEKS PENGELOLAAN BARANG MILIK DAERAH (BMD) DI DINAS PEKERJAAN UMUM PROVINSI SULAWESI UTARA - Nendher, Joindra; May, Gordon Angel; Londa, Cliver; Tinangon, Jantje J. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Office of Public Works – Human Settlements and Spatial Planning is an Agency that engaged in infrastructure matter. In carrying out its functions Office of Public Works has a regional government facilities which named Goods for Regional Government, what is meant by Goods for Regional Government is a any goods obtained or purchased from Regional Development Budget. To support regional asset management effectively and efficiently and to create transparency in regional asset management policy, therefore regional government needs to own or develop management information system  that reliable as a tool to create pattername’s report.Keywords : Goods for Regional Government